Ritual Pangewarang - Wahyu Chandra (Universitas Muslim Maros, 2019)
Pangewarang is an eight-year ritual of the Kaluppini indigenous community in Enrekang Regency, South Sulawesi. This ritual is a form of acculturation between Islamic and pre-Islamic beliefs. In many parts of this ritual, there are Islamic elements in it. This ritual has also become the Islamic identity of the Kaluppini people, which is different from other communities. This study was conducted using qualitative approach. There 19 informants participated in this study, consisting of three religious leaders, four traditional figures, two shaman (sando), chair of Aliansi Masyarakat Adat Nusantara (AMAN) Massenrempulu, three community leaders and six members of the Kaluppini community. Data was collected using the combination of observation and in-depth interview. The results shows that the implementation of the Pangewarang ritual among Kaluppini people indicates how religion and tradition are acculturated, inseparable, and complementary. Besides, the existence of Pangewarang rituals in Kaluppini has also formed an identity and gave meaning to the lives of Kaluppini people. This study is in line with the view of Hans Mol (1986) which states that there are four roles of religion in the formation of the community's identity. First, religious beliefs give a deep meaning to events that occur in society, as well as provide meaning that is fundamental to people's lives. Second, religion forms a transcendental order for a society that has two functions, namely to regulate, organize, and guarantee order in society, as well as a source of legitimacy. Third, religion can awaken and strengthen emotional ties or commitment in society. The sameness of belief and faith is a powerful glue for social ties in society and the fourth is that religion in the form of ritual can strengthen the sense of togetherness in society, which in turn will strengthen the sense of belonging and social identity in a society.